Perencanaan Struktur dengan Sistem Rangka Pemikul Momen Khusus pada Hotel Nawasena di Singkawang - Magfiroh, Jamillatul; Nevilia, Rauda; Rasiwan, Rasiwan; Ariansyah, Rona (Teknik Sipil, Politeknik Negeri Ketapangg, 2025)
Indonesia frequently experiences natural disasters such as earthquakes. This is due to the fact that geologically, Indonesia is located on the convergence of four tectonic plates. Therefore, buildings must be designed to minimize construction failures. According to SNI 2847:2019, one method for designing earthquake-resistant reinforced concrete buildings is the Special Moment Resisting Frame System (SRPMK). The SRPMK system can be applied to the construction of high-rise buildings, such as the Nawasena Hotel in Singkawang, West Kalimantan, with a height of 14 floors. Based on the cone penetration test (CPT), the soil at the construction site is categorized as SD. Additionally, according to the structural response category, the hotel falls into risk category II. The structural planning of the Nawasena hotel used earthquake analysis based on the spectrum response, which refers to SNI 1726:2019. The analysis results obtained 140 mm floor slab and 125 mm roof. Beams used 800/600 mm and 550/450 mm for primary beams, 400/300 mm for secondary beams, and 600/400 mm for tie beams. Columns used 1200/1000 mm and 650/800 mm. The foundation consists of a raft pile with dimensions of 25 m x 41 m (Building A), 19.45 m x 41 m (Building B), and 35.43 m x 41 m (Building C). In Building A, there was a significant drift of 55.396 mm (x-direction) and 52.470 mm (y-direction), requiring shear walls.